"An analysis of the methods and activities in teaching Arabic to the second generation in light of the knowledge explosion." - said.hamoudi, said.hamoudi (El Omda in Linguistics and Discourse Analysis, 2018)
"The 20th century is considered an intellectual revolution that overthrew many old traditions, replacing uncertainty and speculation with experimental analysis. Global developments were marked by astonishing progress in social, scientific, and technical life, as well as their applications. The explosion of human knowledge grew due to the influx of information and knowledge from all corners of the world, with no boundaries or distances to limit it. This directly or indirectly affected our world, with significant repercussions on our social and economic affairs, and especially on the educational system. This is why we contribute, albeit modestly, through this paper by describing the educational reality and recent developments in teaching methods, while attempting to explore innovations in educational systems that combine tradition and modernization—both of which are essential for the educational journey of any society. The focus is on maximizing the benefits of scientific and technological advancements, as well as modern educational efforts and innovations."